2003
DOI: 10.1046/j.1365-3180.2003.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural tolerance of Cuscuta campestris to herbicides inhibiting amino acid biosynthesis

Abstract: The response of Cuscuta campestris Yuncker, a nonspecific above-ground holoparasite, to amino acid biosynthesis inhibitor (AABI) herbicides, was compared with other resistant and sensitive plants in doseresponse assays carried out in Petri dishes. Cuscuta campestris was found to be much more resistant to all AABI herbicides tested. The I 50 value of C. campestris growth inhibition by glyphosate was eightfold higher than that of transgenic, glyphosate-resistant cotton (RR-cotton). The I 50 value for C. campestr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 22 publications
3
31
0
2
Order By: Relevance
“…ha has also been found to reduce field dodder in tomato (Mullen et al, 1998). However, some other studies showed a low susceptibility of C. campestris to some sulfonylurea herbicides (Rubin, 1994) and also that C. campestris seeds germinated without a host in herbicide solutions and even showed a certain degree of tolerance to high concentrations of herbicides that are amino acid biosynthesis inhibitors (Nadler-Hassar & Rubin 2003).…”
Section: Field Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…ha has also been found to reduce field dodder in tomato (Mullen et al, 1998). However, some other studies showed a low susceptibility of C. campestris to some sulfonylurea herbicides (Rubin, 1994) and also that C. campestris seeds germinated without a host in herbicide solutions and even showed a certain degree of tolerance to high concentrations of herbicides that are amino acid biosynthesis inhibitors (Nadler-Hassar & Rubin 2003).…”
Section: Field Trialsmentioning
confidence: 99%
“…Photosynthesis-inhibiting herbicides are therefore assumed to have little power in controlling the parasite, while herbicides that inhibit amino acid biosinthesis may affect field dodder growth (NadlerHassar & Rubin, 2003). A fact that supports the assumption of greater sensitivity of field dodder plants to amino acid-inhibiting herbicides is that the parasite has its own independent pathway of biosynthesis of amino acids (Wolswinkel, 1984).…”
Section: Field Trialsmentioning
confidence: 99%
“…We recently demonstrated that Cuscuta pentagona seedlings use plant volatiles to locate and choose among hosts (Runyon et al, 2006). Once a host is located, C. pentagona vines twine around the host stem and produce haustoria, specialized organs that grow into the host to extract nutrients from both xylem and phloem (Dawson et al, 1994 ) and, because of their close physiological connection to hosts, are difficult to control without also impacting the crop plants (Nadler-Hassar and Rubin, 2003). Despite their economic importance and the profound effects they have on host plants and community dynamics, relatively little is known about the defenses induced by parasitic plant attack or how these defenses affect host plant interactions with other organisms.…”
mentioning
confidence: 99%
“…Moreover, in a recent study we were able to show that when the parasite is grown independently of a host, it can tolerate high concentrations of glyphosate. In addition, application of glyphosate to a parasitized glyphosate-resistant sugar beet host initially injured the parasite, but at a later stage the parasite recovered and resumed normal growth (Nadler-Hassar and Rubin 2003). Collectively, these results indicate that the parasite has some natural mechanism of glyphosate tolerance.…”
Section: Introductionmentioning
confidence: 84%